Polyunsaturated aldehyde production by a temporally varying field assemblage of diatoms in the San Juan Island Archipelago: can diatom metabolites affect microzooplankton grazing? - Paul, Blair M. (Blair Michael) (Western Washington University, 2010)
The success of diatoms in a wide range of global habitats, together with common observations of the post-bloom sinking of diatom biomass, indicates that this taxon has evolved a mechanism to reduce the largest loss process for phytoplankton in the ocean, microzooplankton grazing. Recent research has shown that polyunsaturated aldehydes (PUAs), lipid oxidation products generated by various species of diatoms, can reduce copepod fecundity and egg hatching success. This leads to the question of whether PUAs adversely affect the major global consumers of phytoplankton, microzooplankton. In the late spring to early fall 2007, I used the seawater dilution technique to quantify phytoplankton growth and microzooplankton grazing; at the same time I determined diatom and microzooplankton abundances and biomasses at Rosario Point, Orcas Island, WA (N 48° 38.614, W 122°52.750). In addition, I measured production of PUAs by the phytoplankton community to assess whether these chemicals functioned as chemical grazing deterrents, to look for novel PUA-producing diatom genera, and to evaluate environmental factors that potentially influenced PUA production. Four hydrographic structural change (HSC) events in the water column were identified during the spring-summer sampling period that probably reflected flushing by outside water masses. These events altered environmental conditions with distinct planktonic communities (termed community states) emerging during post-event water column stabilization. The first two community states were characterized by low nutrient concentrations with chlorophyll a between 6.5 and 13.1μg L-1 and several instances of negative growth and grazing rates. This suggested the release of an unidentified chemical by the Pseudo-nitzschia spp. dominated first community state that additionally had moderately high PUA production levels of 771-1520 μg PUA g C-1. Harmful algal bloom species Heterosigma akashiwo dominated the mid-summer community state with chlorophyll a reaching 10.45 μg chl L-1 and microzooplankton grazing rates reduced to nearly zero. Lastly, the diatom dominated mid-to-late summer community state reached 15.84 μg chl L-1 with Thalassiosira spp, Chaetoceros spp., and Skeletonema sp. all present as major constituents of the community that produced high PUA levels (1280- 3410 μg PUA g C-1). Each of the genera found in this study contain species that have previously been identified as producing PUA. Low phosphate concentrations within each of the PUA-producing communities appeared to influence production, as well as the presence of low light levels in the first community state that possibly increased PUAprecursor molecule formation. Furthermore, changes to growth rates in the >20-μm (diatom) community with nutrient addition often occurred during PUA production, however this response by sampled diatom communities did not preclude PUA production. Community grazing on the >20-μm size fraction was observed to decrease when PUA production was high. During the spring state negative grazing along with low microzooplankton biomass made interpretation difficult. During the mid-to-late summer state grazing was reduced to -0.02 to 0.08 d-1 with a large biomass of 143 to 180 μg C L-1 of non-feeding microzooplankton that included known diatom-feeding dinoflagellates Protoperidinium sp., 40 to 59 μm Gyro/Gymnodinium, and >60-μm Gyro/Gymnodinium. With this reduced grazing, diatoms grew from 23.2 to 244 μg C L-1. Since diatom grazing genera of microzooplankton did not feed during the initiation and maintenance of the August bloom, my data suggests that PUA played a role in bloom initiation and allowed the diatom community to avoid predation.